Metabolomic Differential Compounds Reflecting the Clinical Efficacy of Polyethylene Glycol Recombinant Human Growth Hormone in the Treatment of Childhood Growth Hormone Deficiency - Li, Ji; Pan, Weiwei; Qian, Jianqin; Ni, Yan; Fu, Junfen; Ni, Shaoqing (Frontiers in Pharmacology, 2022)
Understanding the metabolite profiles may aid in providing a reference for the individualized treatment of PEG-rhGH. Therefore, this study aimed to evaluate the clinical efficacy of PEG-rhGH in GHD patients by using a metabolomic approach. Fifty-seven pediatric participants treated with PEG-rhGH in this study were enrolled (28 GHD patients with high clinical efficacy and 29 GHD patients with lower clinical efficacy). Serum samples from all patients at baseline were first collected for biochemical detection, followed by metabolite detection using gas chromatography time-of-flight mass spectrometry. The candidates included heptadecanoic acid, stearic acid, 2-hydroxybutyric acid, myristic acid, palmitoleic acid, D-galactose, dodecanoic acid, and oleic acid. The related metabolic pathways involved fatty acid metabolism and energy metabolism. This study suggested that growth gains of PEG-rhGH might be differentiated by altered serum levels of fatty acid. Collectively, the metabolomic study provides unique insights into the use of PEG-rhGH as a therapeutic strategies for the individualized treatment.